Genome-wide interaction study of dietary intake of fibre, fruits, and vegetables with risk of colorectal cancer - Papadimitriou, Nikos; Kim, Andre; Kawaguchi, Eric S.; Morrison, John; Diez-Obrero, Virginia; Albanes, Demetrius; Berndt, Sonja I.; Bézieau, Stéphane; Bien, Stephanie A.; Bishop, D Timothy; Bouras, Emmanouil; Brenner, Hermann; et al. (EBioMedicine, 2024)
Background - Consumption of fibre, fruits and vegetables have been linked with lower colorectal cancer (CRC) risk. A genome-wide gene-environment (G × E) analysis was performed to test whether genetic variants modify these associations. - Methods - A pooled sample of 45 studies including up to 69,734 participants (cases: 29,896; controls: 39,838) of European ancestry were included. To identify G × E interactions, we used the traditional 1--degree-of-freedom (DF) G × E test and to improve power a 2-step procedure and a 3DF joint test that investigates the association between a genetic variant and dietary exposure, CRC risk and G × E interaction simultaneously. - Findings - The 3-DF joint test revealed two significant loci with p-value <5 × 10−8. Rs4730274 close to the SLC26A3 gene showed an association with fibre (p-value: 2.4 × 10−3) and G × fibre interaction with CRC (OR per quartile of fibre increase = 0.87, 0.80, and 0.75 for CC, TC, and TT genotype, respectively; G × E p-value: 1.8 × 10−7). Rs1620977 in the NEGR1 gene showed an association with fruit intake (p-value: 1.0 × 10−8) and G × fruit interaction with CRC (OR per quartile of fruit increase = 0.75, 0.65, and 0.56 for AA, AG, and GG genotype, respectively; G × E -p-value: 0.029). - Interpretation - We identified 2 loci associated with fibre and fruit intake that also modify the association of these dietary factors with CRC risk. Potential mechanisms include chronic inflammatory intestinal disorders, and gut function. However, further studies are needed for mechanistic validation and replication of findings. - Funding - National Institutes of Health, National Cancer Institute. Full funding details for the individual consortia are provided in acknowledgments.